2019
DOI: 10.3390/ijtpp4020015
|View full text |Cite
|
Sign up to set email alerts
|

Flutter Analysis of a Transonic Steam Turbine Blade with Frequency and Time-Domain Solvers

Abstract: The aim of this study was to assess the capabilities of different simulation approaches to predict the flutter stability of a steam turbine rotor. The focus here was on linear and nonlinear frequency domain solvers in combination with the energy method, which is widely used for the prediction of flutter onset. Whereas a GMRES solver was used for the linear problem, the nonlinear methods employed a time-marching procedure. The solvers were applied to the flutter analysis of the first rotor bending mode of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The higher pressure harmonics are one order of magnitude below the first one, but they are present around the shock impingement region although the vibration amplitude already reported is quite low. To further confirm the excellent agreement between TRAF and TRACE, the authors also include in the plot the single value of damping obtained with the non linear version of TRACE for the most unstable nodal diameter (see Frey et al (2019)): TRAF and TRACE practically predict the same value. An additional qualitative comparison can be done by looking at the local work distribution on the blade surface for the most unstable nodal diameter nd=+13 (see Fig.…”
Section: Unsteady Flutter Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The higher pressure harmonics are one order of magnitude below the first one, but they are present around the shock impingement region although the vibration amplitude already reported is quite low. To further confirm the excellent agreement between TRAF and TRACE, the authors also include in the plot the single value of damping obtained with the non linear version of TRACE for the most unstable nodal diameter (see Frey et al (2019)): TRAF and TRACE practically predict the same value. An additional qualitative comparison can be done by looking at the local work distribution on the blade surface for the most unstable nodal diameter nd=+13 (see Fig.…”
Section: Unsteady Flutter Resultsmentioning
confidence: 81%
“…Starting from this geometry, the open flutter test case has been established by Qi et al (2017) by the definition of flow conditions (compatible with steam turbine at design conditions) and blade structural characteristics. The numerical flutter test-case is already fully described in previous publications (Qi et al (2017); Frey et al (2019)) and only the main information are reported hereafter. The stage depicted in Fig.…”
Section: Numerical Test Casementioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional non-reflecting boundary conditions are applied throughout the study. The solver has been validated against other established codes [19,20].…”
Section: Flow Solvermentioning
confidence: 99%
“…The current state-of-the-art technique relies on solving the steady Reynolds-averaged Navier-Stokes (RANS) equations with second-order accurate finite volume schemes in combination with appropriate RANS models, analyzing the steady-state flow field. Unsteady effects are assessed using unsteady RANS approaches or, to save computation time, frequency domain methods such as harmonic balance [1,2]. Yet, all the mentioned steady and unsteady approaches include RANS models, which are generally well tuned and mature at and close to the aerodynamic design points.…”
Section: Introductionmentioning
confidence: 99%